Evaluation of accuracy of electronic apex locators in the presence of various irrigants: an in vitro study (LLC "Endo Press", 2020)
The determination of an accurate root canal working length is a critical step in endodontic therapy. Modern electronic apex locators are believed to be able to perform well in the presence of various liquids. However, some reports suggest that accuracy of electronic apex locators is dependent on the type of irrigation solution used. The aim of this in vitro study was to evaluate the accuracy of EndoEst-Apex 02 and Root ZX, electronic apex locators, in the presence of various irrigants. In the present study the use of 3% NAOCL, 2% Chlorhexidine, 17% EDTA affected the accuracy of the apex locators in determining working length.